Analysis of Workplace Facilities Influence on ATC Performance at AirNav Jakarta ACC Unit - Awangku Muhammad Z; Nunuk Praptiningsih; Gilang Trio Putra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the influence of workplace facilities on the performance of Air Traffic Controllers (ATC) at the Area Control Centre Unit of AirNav, Jakarta Air Traffic Service Centre (JATSC). Facilities such as communication systems, radar displays, and supporting infrastructure are critical to aviation safety and operational efficiency. Issues like illegal radio signals, frequency interference, and radar shadowing can disrupt communication and reduce ATC performance. The research employs a quantitative approach with a positivist paradigm to obtain objective, numerical data. From a population of 238 ATC personnel, 79 respondents were selected using simple random sampling based on Slovin’s formula. Data collection methods included questionnaires, documentation, and secondary data. Data analysis was conducted using statistical software through stages of data cleaning, variable coding, descriptive analysis, and correlation testing using Pearson or Spearman methods. The questionnaire assessed ATC perceptions of workplace facilities, while documentation and secondary data provided contextual support. The findings are expected to contribute theoretically to human resource and occupational safety literature, and practically support AirNav Indonesia in evaluating and improving workplace facilities to enhance air traffic control performance and aviation safety